Natural revegetation of areas impacted by gold mining in the tropical rain forest of Chocó, Colombia - Valois-Cuesta, Hamleth; Martínez-Ruiz, Carolina; Quinto-Mosquera, Harley (Revista de Biología Tropical, 2022)
Introduction: Ecological restoration is a strategy that allows recovering goods and services in disturbed ecosystems. One of the activities that generates greatest impact on forest ecosystems is open pit mining, as it causes strong changes in the structure and functioning of these systems. Objective: The aims of this work was to evaluate the effect of successional age and distance to the adjacent forest (reference forest) on the biological structure and composition of the plant community in abandoned gold mines in the tropical rain forest of Chocó in Colombia. Methods: Between June and December 2012, and June and October 2021, vegetation sampling was carried out in mines with 6, 10, 15, 19 and 24 years of abandonment and in the reference forest. In each mine of different ages and the reference forest, four 2×50 m plots were established and distributed perpendicularly to the edge of the forest, at 50 m and 100 m distance (two plots per distance) taking as a starting point split the forest-mine edge (ecotone). Results: 300 species, 193 genera and 75 families were identified. The richness, diversity, and evenness changes little with the time of abandonment in the mines but reaches higher values in the reference forest. Species composition is similar between mines but differs substantially from the reference forest (only 7% similarity). Conclusions: The results suggest that 24 years is a short time to appreciate a substantial recovery of the biological structure and composition of the vegetation in mines if it is compared with the reference forest where the richness, diversity, evenness are higher and the composition of species differs substantially. Although the distance to the adjacent forest seems to have no effect on these variables, it is clear that other factors such as the quality of the substrate and the reproductive strategies of some herbaceous species of the families Cyperaceae and Melastomataceae, as well as some trees such as Cespedesia spathulata and Miconia reducens, they play an important role in the early natural revegetation of abandoned mines in the pluvial forests of the Colombian biogeographical Chocó.